(untitled) (Research, Society and Development, 2020)
This study aims to analyze the mitigation caused to the immigrant’s inherent rights due to the elaboration of Ordinance MJ No. 666/2019, taking as a parameter the normative provisions based on the defense of human rights. In this perspective, this article, through descriptive research, deductive method, collection of documentary and bibliographic data, proceeded in order to carry out a legal analysis of Ordinance MJ No. 666/2019 in the light of the Universal Declaration of Human Rights, as well as 1988 Federal Constitution and Law No. 13,445/2017. Notwithstanding, it also elucidated the main inconsistencies regarding the violation of the principles of legality, due process and its corollaries, with the creation of indeterminate and generic terms of “dangerous person” and “act contrary to the principles and objectives set out in the Constitution. Federal”, as well as the summary deportation institute. Finally, in view of the exposed problem, it was sought, based not only on the aforementioned principles, but also on the presumption of innocence, ample and contradictory defense, access to justice and reasonable duration of the process, to clarify the need of the State, based on defense of human rights and respect for the immigrant’s well-being, seek border ordering and adequate migratory control, in view of the substantial inconveniences caused to the Democratic Rule of Law by non-observance of these guarantees.